Productivity with General Indices ofManagement and Technical Change - Thomas Triebs; Subal C. Kumbhakar (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
We propose a model of production where technical change is both time and management induced. We define a general management index in addition to the general time index of Baltagi and Griffin (1988) and use them as arguments in the translog productionfunction. Time and management induced technical change are then defined interms of these general indices. For comparison, we also consider models in which time and management are specified as continuous variables. We report empirical results for a sample of manufacturing firms in the US, UK, Germany and France.
Keywords: M11; D24; O33; 330; General management index; general time index; technical change; Produktivität; Technischer Fortschritt; Zeit; Management; Index; Theorie; Schätzung; Verarbeitendes Gewerbe; USA; Großbritannien; Deutschland; Frankreich